State-dependent µ-opioid Modulation of Social Motivation – a model - Loseth, Guro E.; Ellingsen, Dan-Mikael; Leknes, Siri (Frontiers in Behavioral Neuroscience, 2014)
Social mammals engage in affiliative interactions both when seeking relief from negative affect and when searching for pleasure and joy. These two motivational states are both modulated by µ-opioid transmission. The µ-opioid receptor (MOR) system in the brain mediates pain relief and reward behaviours, and is implicated in social reward processing and affiliative bonding across mammalian species. However, pharmacological manipulation of the µ-opioid system has yielded opposite effects on rodents and primates: in rodents, social motivation is generally increased by MOR agonists and reduced by antagonists, whereas the opposite pattern has been shown in primates. Here, we address this paradox by taking into account differences in motivational state. We first review evidence for µ-opioid mediation of reward processing, emotion regulation, and affiliation in humans, non-human primates, rodents and other species. Based on the consistent cross-species similarities in opioid functioning, we propose a unified, state-dependent model for µ-opioid modulation of affiliation across the mammalian species. Finally, we show that this state-dependent model is supported by evidence from both rodent and primate studies, when species and age differences in social separation response are taken into account.